NANO-STRUCTURED Nd-Fe-B THIN FILMS DEPOSITED ON GLASS SUBSTRATE BY FLASH EVAPORATION METHOD - POPESCU, Ana-Maria; ANASTASESCU, Mihai; CALDERON MORENO, Jose; NEACSU, Elena Ionela; DEMIDENKO MINCHUKOVA, Olga; YANUSHKEVICH, Kazimir; CONSTANTIN, Virgil (Studia Universitatis Babeș-Bolyai Chemia, 2025)
Nd-Fe-B nanostructured thin layers have been growth on the glass substrate by the "flash" evaporation (FE) method. The microscopic and surface structure analysis of the Nd-Fe-B thin films investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM) and X-ray photoelectron spectroscopy (XPS) demonstrate these thin films to be nanostructured.The temperature dependence of the specific magnetization of the films in the 80 ≤ T ≤ 800 K range, measured by the ponderomotive method showed that the magnetization of the Nd-Fe-B nanostructured thin films before corrosion did not exceed 85 A×m2×kg-1 at 77 K. In such Nd-Fe-B nano thin films the long-range structural order is destroyed. After corrosive action on the thin films, their specific magnetization value increased to 140-155 A×m2×kg-1, most probably because of the formation of Fe3O4 (iron oxide) and the presence of free iron ions on the surface of the nanometric Nd-Fe-B layer upon heating the samples to 1050 K. XPS spectra confirmed the presence of Fe3O4, FeOOH and Nd(OH)3.